Development of Sempolan YGG MSME Products in Kunduran Village - Rohman, Fatchur; Nabila, Azzahra (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2023)
Kunduran is a sub-district in Kunduran sub-district, Blora which is the capital of Kunduran sub-district, Kunduran sub-district is very busy like a city, this sub-district is also one of the sub-districts in Blora district out of 25 sub-districts in Blora Regency. To the west are Gagaan and Sambiroto Villages, to the east are Jagong Village, to the south are Bakah and Gagaan Villages, and to the north are Bejirejo and Sambiroto Villages. Based on the condition of the area, the economic potential of the Kunduran sub-district comes from the agricultural sector and home industry. Mrs. Gunarti's Sempolan business is one of the businesses operating in the food industry, namely in Sempolan which is given Sempolan YGG. The results of the Kunduran KKN team's observations of Mrs. Gunarti's home industry can be explained that Mrs. Gunarti's sempolan business is not yet innovative and creative in terms of logo and packaging, and is long-lasting, and its target market is only targeting the local market around the Kunduran market. Even though this business requires product development, new product development is closely related to the success of a company in its efforts to increase sales. The aim of providing service to the assisted living industry is to develop products, namely strengthening, managing and expanding the market for Mrs. Gunarti's business or SMEs so that they can compete with other home industry products